ISLAMIC RELIGIOUS EDUCATION LEARNING POLICY MODEL - Ginting, Nurman; Fariz, Miftah; Hasanuddin, Hasanuddin (Proceeding International Seminar of Islamic Studies, 2022)
In arranging for education in a country to take place properly and achieve the educational goals aspired to, various policies are carried out, including in this case also related to religious education which is also part of the policy. Education policy in a country depends on the political system adopted so that each country has different policies. Indonesia adheres to a democratic system based on law. Decided policies must also be based on legislation. There are several policies taken by the government in order to improve the quality of religious education that are expected to solve the multidimensional crisis in the country, which are related to moral-ethical aspects and at the same time want to describe the meaning of National education. In establishing these various policies, of course, it cannot be separated from the theories and concepts of public policy. These theories and concepts are formulated to be used in realizing what is expected. Moving on from this, we can see the use of policy models used, to reflect the aspects that want to be developed in the educational process